PENGARUH LEVERAGE DAN LIKUIDITAS TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR BASIC MATERIALS INDUSTRI CONSTRUCTION MATERIALS YANG TERDAFTAR DI BEI PERIODE 2017 - 2023 - Aulia, Muhayatul; Andriyani, Hapsari (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of leverage and liquidity on Financial distress in Basic Materials Industry Construction Materials companies listed on the Indonesia Stock Exchange (IDX) in the period 2017 - 2023. This study is motivated by the problem of oversupply in the cement industry which causes a decline in the company's financial performance and increases the risk of Financial distress. Financial Distress is a condition of declining financial health of a company that occurs before bankruptcy. The leverage variable is measured using the Debt To Asset Ratio (DAR) while the Current Ratio (CR) and Financial distress are measured using the Altman Z-Score method. The research method used is a quantitative approach with panel data regression analysis. The sampling technique uses the Purposive Sampling method, with a total of 4 (Four) companies namely INTP, SMBR, SMGR, SMCB. The results of this study indicate that partially leverage measured using the Debt To Asset Ratio (DAR) has a significant negative effect on Financial distress while liquidity measured using the Current Ratio (CR) has a significant positive effect on Financial distress and simultaneously or together leverage and liquidity have a significant positive effect on Financial